ORGANIZING MODERN STRUCTURE OF STATE FINANCE CONTROL IN RUSSIAN STATE SYSTEM - Alina M. Minitaeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses issues of organizational support necessary for shaping the efficient system of state finance control through assessing the results of its work. The place of various bodies of state finance control was shown in the organizational structure of its system, as well as its functional orientation, structure, strength and characteristics of staff, material, technical, finance, information and other support of the body, peculiarities of interaction and order of functional and administrative subordination within the body. The article shows the structure of relations between different bodies of state finance control, which depends on many factors, for example aims and objectives of the body, state structure, principles of state management, development of state systems. The author puts forward key ways of organizing and developing modern system of state finance budget control in Russia.